Children Tv Series As Commodity In Culture Industry - Okditazeini, Vannyora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This paper will elaborate the struggle of Jalan Sesama TV series in the mid of media and commodities rivalry in the culture Industry. Library research was carried out in doing meta synthesis analysis by exploring the concept of commodity proposed by Theodor Adorno. From the conceptual elaboration, it was found that media still provide place for Jalan Sesama TV Series to do its creation. However, sooner or later, it will be banished and became a weird TV series among others.